OBSERVATIONS, PERCEPTIONS ET ADAPTATIONS AU CHANGEMENT CLIMATIQUE DANS LA SOUS-PRÉFECTURE DE SÉGUÉLA (CÔTE D’IVOIRE) - YAO-KOUASSI, Quonan; ADAYÉ, Kouassi Albert; KOUADIO, Konan Célestin; COULIBALY, Yardjouma Esai (International Journal of Scientific Research and Management (IJSRM), 2021)
In a context of sustainable development and food security, the fight against climate change has become a priority. In tropical rural areas, its effects are beginning to appear by affecting agricultural production, which is a factor that aggravates socio-economic impacts. Indeed, understanding the determinisms of climate change as well as their perception and the adaptation strategies developed by rural populations is an issue of food security and socio-economic development. In the sub-prefecture of Séguéla, the perceptions and adaptations to climate change of populations living from rain-fed agriculture are acute. This article analyzes on the one hand the climatic variability of this sub-prefecture based on scientific observations of the annual accumulations of precipitation from 1986 to 2015. And on the other hand, following a questionnaire survey, the perception and representation of this climatic variability as well as the strategies developed in response by farmers were noted. The main results indicate a decrease in rainfall in general modifying the crop calendar of farmers. In addition, the study attests that peasant perceptions and representations are linked to their local beliefs. This then results in dynamics and modalities of adaptation through the introduction of new cultures / associations of cultures, the development of lowlands reflecting the interactions of the peasant population with its environment.